9:3>9:3
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{3^{19}.2^9+5.9^9.2^9}{3^{19}.2^9+9^{10}.2^{10}}\)
\(=\frac{3^{19}.2^9+5.\left(3^2\right)^9.2^9}{3^{19}.2^9+\left(3^2\right)^{10}.2^{10}}\)
\(=\frac{3^{19}.2^9+5.3^{18}.2^9}{3^{19}.2^9+3^{20}.2^{10}}\)
\(=\frac{3^{18}.2^9\left(3+5\right)}{3^{19}.2^9\left(1+6\right)}\)
\(=\frac{8}{3.7}=\frac{8}{21}\)
Sửa đề : \(\frac{3}{7\cdot9}+\frac{3}{9\cdot11}+\frac{3}{11\cdot13}+...+\frac{3}{57\cdot59}\)
\(=\frac{3}{2}\left[\frac{2}{7\cdot9}+\frac{2}{9\cdot11}+\frac{2}{11\cdot13}+...+\frac{2}{57\cdot59}\right]\)
\(=\frac{3}{2}\left[\frac{1}{7}-\frac{1}{9}+\frac{1}{9}-\frac{1}{11}+...+\frac{1}{57}-\frac{1}{59}\right]\)
\(=\frac{3}{2}\left[\frac{1}{7}-\frac{1}{59}\right]=\frac{78}{413}\)
P/S : Thi gặp dạng này thì dễ rồi -_-
\(\frac{3}{7.9}+\frac{3}{9.11}+\frac{3}{11.13}+...+\frac{3}{57.59}\)
\(=\frac{3}{2}.\left(\frac{2}{7.9}+\frac{2}{9.11}+\frac{2}{11.13}+...+\frac{2}{57.59}\right)\)
\(=\frac{3}{2}.\left(\frac{1}{7}-\frac{1}{9}+\frac{1}{9}-\frac{1}{11}+\frac{1}{11}-\frac{1}{13}+...+\frac{1}{57}-\frac{1}{59}\right)\)
\(=\frac{3}{2}.\left[\frac{1}{7}+\left(\frac{1}{9}-\frac{1}{9}\right)+\left(\frac{1}{11}-\frac{1}{11}\right)+\left(\frac{1}{13}-\frac{1}{13}\right)+...+\left(\frac{1}{57}-\frac{1}{57}\right)-\frac{1}{59}\right]\)
\(=\frac{3}{2}.\left[\frac{1}{7}-\frac{1}{59}\right]\)
\(=\frac{3}{2}.\frac{52}{413}=\frac{78}{413}\)
a) x - 3 = -6 => x = ( -6 ) + 3 => x = -3
b) x - ( -5 ) = 4 => x = 4 + ( -5 ) => x = -1
c) x - ( -9 ) = 4 - ( -9 ) => x = 4
d) 4 - x = -3 - ( -6 ) => x = 4 - [ ( -3 ) - ( -6 ) ] => x = 1
\(\frac{\left(a+b\right)^3}{ab+9}+\frac{2}{3}\left(ab+9\right)+12\ge6a+6b\)
\(\Sigma\frac{a^3+b^3}{ab+9}\ge\frac{1}{4}\Sigma\frac{\left(a+b\right)^3}{ab+9}\ge\frac{1}{4}\left(12\left(a+b+c\right)-\frac{2}{3}\left(\frac{\left(a+b+c\right)^2}{3}+27\right)-36\right)=9\)
\(9\div3=3\div9\) vì
\(3=3\)